Wskaźnikowa analiza płynności finansowej w świetle nowelizacji ustawy o rachunkowości - Koza, Andrzej (The ratios analysis of financial liquidity due to amended act of accountancy, 2007)
The liquidity ratios make up the main instruments of opinion of financial liquidity. Data contained in them come from the balance sheet of enterprise. Therefore the shape of source data as well as their range are the condition of correctness of analysis. The introduced changes in law concerning accountancy in reference to the shape of balance extort the modifications of liquidity ratios. The introduced changes in law accountancy became calculate in summers the comparability of results of liquidity ratios till 2001 and after with problems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 189-196